Testicular‐sparing surgery for bilateral or monorchide testicular tumours: a multicenter study of long‐term oncological and functional results. (16th August 2014) - Ferretti, Ludovic; Sargos, Paul; Gross‐Goupil, Marine; Izard, Vincent; Wallerand, Hervé; Huyghe, Eric; Rigot, Jean‐Marc; Durand, Xavier; Benoit, Gerard; Ferriere, Jean‐Marie; Droupy, Stéphane
<x xml:space="preserve">Abstract</x> Objective To review long‐term oncological and functional outcomes of testicular‐sparing surgery (TSS) in men presenting with bilateral or monorchide testicular tumours at one of five reference centres for testicular neoplasm and infertility. Patients and Methods We review 25 cases of bilateral synchrone and metachrone testicular tumours treated in five academic centres between 1984 and 2013. Clinical, biological, ultrasonography and pathological tumour findings, overall survival (OS) times, local or metastatic recurrence, pre‐ and postoperative hormonal profile, paternity and the need for androgen substitution were assessed. Results Eleven patients with a bilateral synchrone tumour and 14 patients with a testicular tumour on a solitary testicle underwent a tumorectomy. The mean (sem) patient age was 31.9 (1.04) years, total testosterone level was 4.5 (0.57) ng.mL and tumour size was 11.66 (1.49) mm. Tumour types were as follows: 11 seminoma, nine non‐seminomatous or mixed germ cell tumours, four Leydig tumours, and one hamartoma. Frozen‐section examination was performed in 14 patients, and matched the final pathological analysis in 11 patients. There was an OS rate of 100% and three patients (12%) presented with a local recurrence after a mean follow‐up of 42.7 months. Radical orchiectomy was performed for six patients. No patient with a preserved testicle required androgen therapy; the mean postoperative total testosterone level was 4.0 ng/mL. No patient remained fertile after radiation therapy. Conclusions TSS for bilateral testicular tumour is safe and effective in selected patients, and should be considered to avoid definitive androgen therapy. Adjuvant radiotherapy remains poorly described in the literature, leading to adjuvant treatment heterogeneity for testicular tumours.